Über die Bedeutung der objektiven und der subjektiven Deduktion der Kategorien - Moledo, Fernando (2015)
In the preface to the first edition of the Critique of Pure Reason Kant refers to two deductions of the categories: the objective and the subjective deduction (KrV, A XVII). This well-known reference possesses several problems of interpretation and has been widely addressed in the specialized literature. Regarding this reference, the accepted interpretation is that both deductions refer to two different tasks of one and the same deduction: the transcendental deduction of the categories. There is nevertheless a widely overlooked passage in the Critique of Pure Reason that suggests a different interpretation on the issue. This passage is to be found in the transcendental Dialectic in the context of the discussion about the possibility of a deduction of the transcendental ideas (KrV, A 336/B 393). According to this passage I will argue in this paper that the objective deduction of the categories corresponds to the transcendental deduction of the categories while the subjective deduction of these concepts corresponds to the metaphysical one.